Fatores de risco associados à disfunção temporomandibular dolorosa em adolescentes - Fernandes, Giovana [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
In order to better understanding the temporomandibular disorder (TMD) pain and the sleep bruxism in adolescents, it is important to study the associated factors associated. Therefore, the aims of the present cross sectional study were to investigate the potential predictor factors for TMD pain and sleep bruxism in adolescents, thereby including factors from the biopsychosocial and multifactorial model, respectively. Moreover, it was test the hypothesis that TMD pain could act as a confounder variable in the association between psychosocial factors and sleep bruxism. One thousand and ninety-four adolescents, aged 12-14 years, composed the sample. The presence of TMD pain was assessed using the RDC/TMD Axis I, and the possible sleep bruxism was diagnosed by self-report. Apart from demographical characteristics, the roles of parafunctional habits, psychosocial aspects, menarche, and other bodily pain complaints were evaluated for TMD pain. The gender, the sleep bruxism family history, and psychosocial factors were evaluated for sleep bruxism. Single and multiple logistic regression models showed that TMD pain was associated with sleep bruxism (OR=1.8 95% CI=1.34-2.34), awake bruxism (OR=2.1 95% CI=1.56-2.83), other parafunctional habits (OR=2.2 95% CI=1.17-4.08), and bodily pain complaints (OR=5.0 95% IC=3.48-7.28). Likewise, sleep bruxism was associated with gender (OR=1.8 95% CI=1.34-2.37), positive sleep bruxism family history (OR=2.5 95% CI=1.83-3.32), and anxiety (OR=1.6 95% IC=1.08-2.22). There were no signs of multicollinearity. The analysis of TMD pain as a third variable revealed a confounding effect in the association between sleep bruxism and anxiety, because a previously significant association (OR=1.6 95% IC=1.08-2.22), became non-significant after testing (OR=1.4 95% IC=1.00-2.05). In summary, parafunctional habits and other bodily pain complaints associated factors to TMD pain in ... (Complete abstract electronic access below)

A fim de melhor entender a disfunção temporomandibular (DTM) e o bruxismo do sono em adolescentes, é importante investigar os fatores de risco associados com sua presença. Portanto, o objetivo do presente estudo transversal foi investigar potenciais fatores de risco, incluídos no modelo etiológico biopsicossocial da DTM dolorosa, assim como na etiologia multifatorial do bruxismo do sono. Além disso, foi testada a hipótese de que a DTM dolorosa poderia atuar como uma variável de confusão na associação entre o bruxismo do sono e os fatores psicossociais. A amostra foi composta por 1.094 adolescentes, de 12 a 14 anos de idade. A presença de DTM dolorosa foi avaliada por meio do eixo I do RDC/TMD, enquanto que o diagnóstico de possível bruxismo do sono foi avaliado por meio do relato do adolescente. Além das características demográficas, os fatores de risco estudados para a DTM dolorosa foram os hábitos parafuncionais, aspectos psicossociais, menarca e dores em outras partes do corpo. O gênero, o antecedente de história familiar e os aspectos psicossociais foram os fatores de risco estudados para o bruxismo do sono. Os modelos de regressão uni e multivariado revelaram que a DTM dolorosa estava fortemente associada com o bruxismo do sono (OR=1,8 95% IC= 1,34-2,34), apertamento diurno (OR=2,1 95% IC= 1,56-2,83), outros hábitos parafuncionais (OR= 2,2 95% IC= 1,17-4,08) e dores em outras partes do corpo (OR= 5,0 95% IC= 3,48-7,28). Do mesmo modo, o bruxismo do sono foi fortemente associado ao gênero (OR=1,8 95% IC= 1,34-2,37), antecedente de história familiar positiva para bruxismo do sono (OR=2,5 95% IC= 1,83-3,32) e ansiedade (OR=1,6 95% IC= 1,08-2,22). Não foram encontrados sinais de multicolinearidade. A análise da DTM dolorosa como terceira variável revelou que ela atua como variável de confusão na associação entre bruxismo do sono e ansiedade, pois a associação...(Resumo completo clicar acesso eletrônico)
Keywords: Adolescentes; Bruxismo; Dor facial; Adolescent